THE INFLUENCE OF VILLAGE HEAD’S LEADERSHIP STYLE ON VILLAGE DEVELOPMENT PERFORMANCE - Zainul Ulum; Muhammad Firdaus; Muhaimin Dimyati (MBA - Journal of Management and Business Aplication, 2023)
The organization achievement is influenced by its employees’ performance that the leaderalways spur the quality performance of his employees by leadership style.Therefore it isnecessary to conduct research on the influence of the village head’s leadership style on thevillage development performance at Mlokorejo Village, Puger District, Jember Regency. Thisstudy aims to test and analyze partially or simultaneously the influence of the village head'sleadership style on development performance. The explanatory research type is used in thisreaserch to examine whether there is a pattern of relationships between two or morevariables. Technique of sampling with population method used 50 villages aparatus ofMlokorejo as respondents. The data analysis shows that the Autocratic, Democratic, andLaisses-Faire leadership style simultaneously have a significant effect on the villagedevelopment performance. Whereas based on the partial test (t test), only the Laisses-Faireleadership style had a significant effect on village development performance, while theautocratic and the democratic leadership style had a partially insignificant effect on thedependent variable of village development performance. It was also shown that the Laisses-Faire leadership style variable (X3) had the most influence on the dependent variable ofvillage development performance (Y).